Dampak Sistem E-Filing, Pengetahuan Perpajakan, Sosialisasi Perpajakan, Kesadaran Wajib Pajak terhadap Kepatuhan Wajib Pajak - I Nyoman Doananda Samadiartha; Gede Sri Darma (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe purpose of this study was to determine the effect of the application of e-filing system, tax knowledge, awareness and dissemination of taxation on taxpayer compliance. The study was conducted quantitatively and using a questionnaire as a tool in data collection. For statistical analysis and hypothesis testing using Structural Equation Modelling (SEM) and processed using the application program AMOS version 22. The respondents in this study is registered taxpayers on the Tax Office Madya Denpasar, taken a sample of 110 corporate taxpayers with a purposive sampling techniques kind of judgment sampling.The results showed that the application of the e-filing system has positive and significant influence on the consciousness of the taxpayer. Knowledge of taxation has positive and significant influence on the consciousness of the taxpayer. Socialization taxation has a positive and significant effect on the consciousness of the taxpayer. Implementation of e-filing system has a positive and significant impact on tax compliance. Knowledge of taxation has a positive and significant impact on tax compliance. Socialization taxation has a positive and significant impact on tax compliance. Awareness taxpayer has a positive and significant impact on tax compliance.The government in this case the Medium Tax Office Denpasar expected to be more emphasis on awareness of taxpayers rather than tax compliance for how tax payers will be obedient in implementing the tax if the awareness of tax obligations is not yet optimal. The taxpayer will be obedient to taxes when first raised awareness of the importance of tax in him. Then the Medium Tax Office Denpasar to be more active to disseminate tax notably e-filing system and the latest tax laws to taxpayers so that taxpayers can implement taxation liabilities with safe, fast and comfortable and the knowledge of the taxpayer can be increased. With increasing knowledge of taxpayers, it is expected to grow within the community of taxpayers to be aware and obedient in implementing taxation liabilities. For the upcoming study is expected to use taxpayer awareness variables as independent variables that can be studied variables influence taxpayer awareness of the other dependent variables.